Influence of tyre pressure and vertical load on coefficient of rolling resistance and simulated cycling performance - Grappe, F.; Candau, R.; Barbier, B.; Hoffman, M. D.; Belli, A.; Rouillon, J. D. (Ergonomics, 1999)
The coefficient of rolling resistance (Cr) for pneumatic tyres is dependent on hysteresis loss from tyre deformation which is affected by the vertical force applied to the tyres (Fv) and the tyre inflation pressure (Pr). The purpose of this paper was to determine the relative influence of five different levels of Pr and four different levels of Fv on Cr and to examine the relationships of Cr with Pr and Fv during cycling locomotion. Fv was modified through carriage of additional mass by the subject. Cr was determined with the coasting deceleration method from measurements performed in a level hallway. Iterations minimizing the sum of the squared difference between the actual deceleration distance and a predicted deceleration distance were used to determine Cr. This latter distance was computed from a derivation based on Newton's second law applied to the forces opposing motion. Cr was described by a hyperbolic function of Pr (Cr = 0.1071 Pr-0.477, r2 = 0.99, p < 0.05), decreasing 62.4% from 150 kPa (Cr= 0.0101) to 1200 kPa (Cr = 0.0038). Fv was related to Cr by a polynomial function (Cr = 1.92.10-8 Fv2 -2.86.10-5 Fv + 0.0142, r2 = 0.99, p = 0.084), with an added mass of 15 kg (Cr = 0.0040) resulting in an 11.4% increase in Cr compared with no added mass (Cr = 0.0035). From this study, it is concluded that the relationships of Pr and Fv with Cr for cycling are non-linear. Furthermore, a simulation model shows that changes in Pr and Fv of the magnitude examined here have an important effect on competitive cycling performance.